The Lady Killer Dalam Lingkungan Perkotaan: Sebuah Studi Fenomenologi - Yansa Mulya; Ratna Djuwita; Hassya Noertalitha Shalsabilla (Asosiasi Psikologi Forensik (Apsifor), 2022)
In patriarchal cultures, women are described as individuals who do not compete much in social environments and tend to avoid conflict. Urbanization makes women do the same activities as men. This study aimed to explore the meaning of female perpetrators before and do committing murder. The criteria for lady killer in this study are individuals living in urban (metropolitan) with female sex over 18 years who are having problems (family, economy, career, romance). This research uses qualitative methods with a phenomenological approach. The results of the study explain that the impact of urbanization creates a faster life process and makes some women who try to follow urbanization become stressed and have no coping. This is due to the unpreparedness of individuals in obtaining continuous negative impacts. When coping stress is doesn’t exist, the individual embed negative emotions continuously until finally deciding to eliminate the